Efficacy and predictors of survival in patients with solitary hepatocellular carcinoma larger than 5 cm undergoing transarterial chemoembolization. Issue 3 (11th May 2021) - Chang, Ke‐Bin; Chi, Chen‐Ta; Lee, Rheun‐Chuan; Hou, Ming‐Chih; Huang, Yi‐Hsiang; Lee, I‐Cheng
Abstract: For patients with solitary hepatocellular carcinoma (HCC) larger than 5 cm not suitable for surgical resection, transarterial chemoembolization (TACE) is an alternative treatment. However, the response rate and survival predictors after TACE remain unclear. This study aimed to evaluate the treatment response and survival in this population. Consecutive 161 treatment‐naïve patients with solitary HCC larger than 5 cm undergoing TACE as the initial treatment were retrospective enrolled. Radiologic response after first TACE was evaluated by modified RECIST criteria. Factors associated with overall survival (OS) were analyzed. Complete response (CR), partial response (PR), stable disease (SD), and progressive disease (PD) were observed in 8.7%, 24.8%, 32.9%, and 36% of patients, respectively. The median OS in patients with CR, PR, SD, and PD were 71.4, 44.8, 17.7, and 14.3 months, respectively. By multivariate analysis, tumor size greater than 10 cm (odds ratio = 0.403, P  = .023) was the only factor associated with radiologic response. By multivariate analysis, ALBI grade 2 or 3 (hazard ratio [HR] = 2.169, P  = .001), tumor size greater than 7 cm (HR = 1.833, P  = .010), and achieving complete or partial response (HR = 0.505, P  = .003) were independent predictors of OS. An ALBI‐Response‐Size (ARS) score was developed to classify patients into low, intermediate and high risk of mortality (median OS of 68.6, 27.1, and 12.5 months, respectively, P  < .001). In conclusion, ALBI grade, tumor size, and radiologic response are important predictors of survival in patients with solitary HCC larger than 5 cm undergoing TACE. A prognostic model can be applied to discriminate patient's survival after TACE.